2023
DOI: 10.1097/hep.0000000000000494
|View full text |Cite
|
Sign up to set email alerts
|

Surrogate and modified endpoints for immunotherapy in advanced hepatocellular carcinoma

Abstract: Background and Aims: Immunotherapies have altered the treatment paradigm in HCC. Surrogate and modified endpoints are used to assess early success in clinical studies and guide clinical practice. We sought to determine whether surrogate endpoints and modifications to the conventional criteria for tumor response (RECIST), including modified RECIST (mRECIST) and immune-modified RECIST (imRECIST), are valid measures to predict overall survival (OS) in HCC treated with immunotherapies. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…The use of progression-free survival as a surrogate marker of overall survival in patients with advanced hepatocellular carcinoma has been challenged. [23][24][25][26] Several trials investigating different systemic therapies, such as REFLECT or COSMIC-312, 27,28 showed significantly longer median progression-free survival but did not find an improvement in median overall survival.…”
Section: Discussionmentioning
confidence: 99%
“…The use of progression-free survival as a surrogate marker of overall survival in patients with advanced hepatocellular carcinoma has been challenged. [23][24][25][26] Several trials investigating different systemic therapies, such as REFLECT or COSMIC-312, 27,28 showed significantly longer median progression-free survival but did not find an improvement in median overall survival.…”
Section: Discussionmentioning
confidence: 99%
“…Many scholars believe that patients with HCC that cannot be resected initially should accept surgery as soon as they meet the criteria of surgery after conversion therapy. However, one study showed that overall survival after resection in HCC patients was correlated with the objective response rate (ORR) of RECIST [34]. Patients with an objective response had longer postoperative OS.…”
Section: Timing Of Surgerymentioning
confidence: 99%
“…Several retrospective studies have compared the prognostic ability of RECIST 1.1 criteria and mRECIST criteria in patients with HCC treated with sorafenib, 10–14 and a recent systematic review that included 34 RCTs highlighted that mRECIST criteria have a better correlation with overall survival (OS) than RECIST 1.1 criteria 15 . In addition, a recent individual-level post hoc analysis of the IMbrave 150 trial and cross-sectional analysis of an international real-world cohort assessed surrogacy of ORR using RECIST, mRECIST, and imRECIST in patients treated with ICI (atezolizumab-bevacizumab, nivolumab, and pembrolizumab) showing that ORR is a good surrogate endpoint for OS in this group of patients as well demonstrating that prognostic performance of mRECST and imRECIST criteria is not higher than that of RECIST 16 . In the IMBrave 150 trial, which led to the worldwide approval of the combination of atezolizumab and bevacizumab (AtezoBev) as the new first-line standard of care for patients with unresectable HCC, 8,17 slightly higher ORR values are reported for mRECIST criteria compared with RECIST 1.1 criteria (33.2 vs. 27.3).…”
Section: Introductionmentioning
confidence: 99%
“…[15] In addition, a recent individuallevel post hoc analysis of the IMbrave 150 trial and cross-sectional analysis of an international real-world cohort assessed surrogacy of ORR using RECIST, mRECIST, and imRECIST in patients treated with ICI (atezolizumab-bevacizumab, nivolumab, and pembrolizumab) showing that ORR is a good surrogate endpoint for OS in this group of patients as well demonstrating that prognostic performance of mRECST and imRE-CIST criteria is not higher than that of RECIST. [16] In the IMBrave 150 trial, which led to the worldwide approval of the combination of atezolizumab and bevacizumab (AtezoBev) as the new first-line standard of care for patients with unresectable HCC, [8,17] slightly higher ORR values are reported for mRECIST criteria compared with RECIST 1.1 criteria (33.2 vs. 27.3). However, the prognostic ability of the two criteria has never been directly compared in patients treated with this combination of systemic treatments.…”
Section: Introductionmentioning
confidence: 99%